Impact of religious proximity on energy trade: Policy implications based on international evidence - Bui, Toan (The Economics and Finance Letters, 2025)
This study aims to examine the role of religious proximity in shaping bilateral energy trade. It explores how shared religious beliefs, values, and practices between countries influence their engagement in the trade of fossil energy resources—specifically coal, oil, and natural gas. The analysis uses a panel dataset comprising 3,407 country pairs from 88 nations over the period 1996–2019. Religious proximity is operationalized through a Grubel–Lloyd index constructed from three religiosity dimensions: religious affiliation, the perceived importance of religion, and attendance at religious services. An extended gravity model is employed to estimate the relationship between religious proximity and energy trade, using Poisson pseudo-maximum likelihood (PPML) to account for heteroskedasticity and zero trade flows. The results reveal a statistically significant negative association between religious proximity and bilateral energy trade. Countries that are more religiously aligned are less likely to engage in energy trade with one another. This relationship holds across various model specifications and sub-periods. Among the three religiosity dimensions, the perceived importance of religion exerts the strongest and most consistent negative effect, particularly during specific historical intervals. Religious proximity, while often assumed to foster cooperation, may instead reflect underlying ideological or cultural barriers that limit economic exchange in energy markets. The findings challenge conventional assumptions about cultural similarity facilitating trade and suggest a more nuanced, context-dependent role of religion in international economic relations. Policy-makers and international energy negotiators should consider cultural-religious dynamics as potential sources of friction in energy cooperation. Understanding the inhibiting role of religious alignment can inform strategies to mitigate soft barriers in trade policy and multilateral energy agreements, particularly in geopolitically sensitive regions.